Circadian timing of injury-induced cell proliferation in Zebrafish - Idda, Maria Laura; Foulkes, Nicholas S. (PLOS ONE, 2012)
In certain vertebrates such as the zebrafish, most tissues and organs including the heart and central nervous system possess the remarkable ability to regenerate following severe injury. Both spatial and temporal control of cell proliferation and differentiation is essential for the successful repair and re-growth of damaged tissues. Here, using the regenerating adult zebrafish caudal fin as a model, we have demonstrated an involvement of the circadian clock in timing cell proliferation following injury. Using a BrdU incorporation assay with a short labeling period, we reveal high amplitude daily rhythms in S-phase in the epidermal cell layer of the fin under normal conditions. Peak numbers of S-phase cells occur at the end of the light period while lowest levels are observed at the end of the dark period. Remarkably, immediately following amputation the basal level of epidermal cell proliferation increases significantly with kinetics, depending upon the time of day when the amputation is performed. In sharp contrast, we failed to detect circadian rhythms of S-phase in the highly proliferative mesenchymal cells of the blastema. Subsequently, during the entire period of outgrowth of the new fin, elevated, cycling levels of epidermal cell proliferation persist. Thus, our results point to a preferential role for the circadian clock in the timing of epidermal cell proliferation in response to injury.